Effect of Temporary Anchorage Devices on class II anterior open bite malocclusion patient - Justin Nguyen; Chris Cramer; Steven Park; Hayden Jones; Ivan Alpizar; Man Hung (Clinical Case Reports)
Key Clinical Message Temporary Anchorage Devices‐supported molar intrusion can be an effective non‐surgical alternative for treating Class II anterior open bite in skeletally mature patients, resulting in an improved occlusal relationship and enhanced chin projection through forward autorotation of the mandible. Abstract Temporary Anchorage Devices are titanium alloy miniscrews utilized to provide maximum orthodontic anchorage during the correction of various malocclusions. This case report examined the use of TADs to support posterior intrusion while correcting a patient's Class II anterior open bite malocclusion in support of the patient's request to avoid surgical intervention.